ANALISIS PERIODE ULANG BANJIR DI KOTA PADANG MENGGUNAKAN CARA IWAI DAN KAITANNYA DENGAN MJO (MADDEN JULIAN OSCILLATION) - Sudiar, Nofi Yendri (IAIN Batusangkar, 2013)
The research has conducted for the analysis of return period of flood over Padang using Iwai?s method. Iwai?s method is a statistical based method to look for a normal distribution. Daily rainfall data observed at seven stations observations were made over the period of analysis to figure out the pattern, then seen his relationship with the MJO. The results of the research obtained monthly rainfall distribution pattern over Padang show equatorial type that has two peaks of rainfall in a year are March and April as the first peak while the second peak in November. Return period rainfall for the 60 days over Padang is 88 mm and is 78 mm in 30 days. Incidence of flooding over Padang in 2000-2010 have a strong relationship with the entry of the MJO phases 3 and 4, is shown from the flood events of 2001, 2002, 2003, 2004, 2006, 2007 and 2009 with a rainfall intensity approaching the calculation of return period 30 - 60 days is 78-88 mm.Key words: Iwai?s Method, return period, flood